Survival outcomes in patients with multiple primary melanomas. (10th April 2015) - Rowe, C.J.; Law, M.H.; Palmer, J.M.; MacGregor, S.; Hayward, N.K.; Khosrotehrani, K.
Abstract Background A substantial number of melanoma patients will develop multiple primary melanomas (MPM). Currently, little is known about the impact of MPM on survival. Objective We aimed to determine whether melanoma survival is worse for patients with MPM compared to those with a single invasive primary melanoma (SPM). Materials and methods A cohort study was conducted. Patients were sourced from an Australian population, with follow‐up information collected retrospectively from registry data. Melanoma‐specific survival analysis was performed to find associated variables after adjustment for known prognostic factors, using four different models, each selecting a different index melanoma lesion. Results 1068 stage I and II melanoma patients were followed up for a median of 24.4 years. MPM was found in 17.8% of the cohort (190 patients), more likely among males and older age groups. Other clinicopathological parameters were similar between the MPM and SPM (878 patients) cohorts. After adjustment for age, sex and Breslow thickness, MPM was a hazard for death from melanoma, across all models, reaching significance when considering the last invasive lesion as the index melanoma (HR = 2.76, P = 0.017). Conclusion Patients with multiple invasive lesions seem more at risk of death from melanoma, independent of known prognostic factors.